COVID-19 Pandemic Outbreak Prompted a Shift in Public Transportation Plans - N, Deepak (Digital Repository of Theses - SSBM Geneva, 2024)
A means of transportation for individuals without accessibility to a motor vehicle and an alternate mode of transportation for commuters is also crucial in reducing the strain on existing infrastructure. Overall, there is compelling evidence in favor of public transportation options. A coronavirus outbreak that started in Wuhan, China in late 2019 spread to entire World. The transportation planning system is complicated and involves many moving parts. Everything from regulating pollution emissions to arranging the construction of major transportation networks, including busways, highways, freeways, and light and heavy rail systems, falls under this category. The aim of the study is to determine the impact of COVID-19 pandemic on public transport usage in India and to find out reasons behind the change in the attitude of the public towards the usage of public transport. In this study, 500 persons were studied from five Indian cities: Kolkata, Mumbai, Indore, Bengaluru, and Delhi. These are the cities with the highest utilization of public transportation. General people are the targeted sample population in this study. The sample size is 500 people from five Indian cities: Kolkata, Mumbai, Indore, Bengaluru, and Delhi. A random sampling Technique was used in this study. The study used both primary data and secondary data. Micro Soft Word, Excel, and SPSS are used in the study. Arithmetic means standard deviation, regression analysis, and correlation are only a few of the statistical methods employed in the study.